Survey on the Application of Assistive Technology in Physical Education - ALIT RAHMAT; ASEP SUMPENA; TETEN HIDAYAT (Journal of Physical Education For Secondary Schools, 2021)
Introduction: Blind students need special services to learn skills that peers usually know; these services include skills in academic matters, orientation and mobility, socio-emotional development, independent living, recreation, career education, sensory efficiency, self-determination, and assistive technology, how important physical education teachers need the assistive technology training needs to get attention. Purpose: This study aims to determine whether assistive technology training in physical education for physical education teachers in Bandung is necessary or not. Methods: The study used a survey method using a questionnaire. This research is quantitative descriptive—the sampling technique used cluster random sampling technique. The research sample is all physical education teachers who are in the Bandung City environment totaling 100 teachers. The instrument used in this research is a simple questionnaire consisting of five survey questions. The data analysis technique used is quantitative descriptive statistics. Results: This study showed that 66% knew assistive technology, 25% said that assistive technology had been applied to physical education learning in schools in Bandung City, 18% said they had attended assistive technology training, 98% of physical education teachers could understand assistive technology after attending this training, and 98% of physical education teachers can add insight related to the implementation of assistive technology in physical education in the city of Bandung. Conclusions: The use of assistive technology in physical education learning can support learning to be more effective, and the creativity of physical education teachers is needed when making effective and efficient assistive technology. Therefore, massive assistive technology training is required for physical education teachers.